1988
DOI: 10.1346/ccmn.1988.0360413
|View full text |Cite
|
Sign up to set email alerts
|

Sintering of Montomorillonites Pillared by Hydroxy-Aluminum Species

Abstract: Abstract--The sintering of montmorillonites pillared by hydroxy-A1 species was investigated by several techniques. The change of the microporosity of the pillared interlayer clay with temperature shows that sintering was mainly due to the loss of microporosity. On calcination of the parent clay at 760~ the X-ray powder diffraction pattern did not change; the 060 line shifted only slightly from 8.988 to 9.017 /k. The infrared (IR) spectrum suggested some dehydroxylation, but the structure appears to have been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
2

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 17 publications
2
19
0
2
Order By: Relevance
“…The detrimental influence of Fe was noted at >700~ in dry air. Tichit et al (1988b) reported that the clay structure itself was destroyed at this temperature, and Mrssbauer spectrometry demonstrated that the environment of Fe 3 § cations was distorted. In the present study, the iron-free clay was more stable, which is consistent with the known lower stability of Fe-OSi bonds compared with AI-O-Si bonds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detrimental influence of Fe was noted at >700~ in dry air. Tichit et al (1988b) reported that the clay structure itself was destroyed at this temperature, and Mrssbauer spectrometry demonstrated that the environment of Fe 3 § cations was distorted. In the present study, the iron-free clay was more stable, which is consistent with the known lower stability of Fe-OSi bonds compared with AI-O-Si bonds.…”
Section: Discussionmentioning
confidence: 99%
“…For montmoriUonite pillared by hydroxy-Al species, bonding was supposed to be ionic, which resulted in weaker bonds. Tichit et aL (1988b) concluded that in this system the thermal stability of the PILC was controlled by the sintering of the pillars at <750~ At >750~ the clay structure itself appeared to be unstable. Several details of the preparation, such as the size of the particles of the original clay, were found to influence the stability of the resulting PILC (Tichit et al, 1988a).…”
Section: Introductionmentioning
confidence: 91%
“…There was an intensity reduction of the main peaks, especially in the stretching mode of the hydroxyl groups at 3627 cm-k This is attributed to the condensation of terminal hydroxyl groups from the polymeric ions in the pillars with the structural hydroxyl groups in the 2:1 layers (Tichit et aL, 1988). Also, there was an intensity reduction of Ai-OH-A1 and AI-OH-Mg vibrational modes at 910 and 842 cm -~, respectively, accompanied by a broadening of the band centered at 1047 cm -1, which is similar to ion-exchanged clays (Tennakoon et al, 1986).…”
Section: Infrared Studiesmentioning
confidence: 95%
“…Valverde et al (2000) however reported a broadening of the Si-O band at 1047 cm -1, which they ascribed to the formation of Si-O-A1 bonds. These authors did not observe the formation of a new A1-O band at ~722 cm -~ owing to the conversion of the A1 polyoxocation to its oxide equivalent as indicated by Tichit et al (1988) and by .…”
mentioning
confidence: 93%
“…Tichit et al (1988) observed that exchange with Al~3 had no effect on the tetrahedral sheet of the montmorillonite based primarily on the absence of changes in the 1125-cm -I (Si-OaP ~"1 stretching mode), the 1035-cm ~ (combined stretching and bending modes Si-Ob"~"~), and 935-cm-~ (A1-OH) bands. A slight shift of the 710-cm -a band towards 735 cm -~ was the only change in the infrared spectrum.…”
mentioning
confidence: 96%